Case Study of a Greenfield Blue Hydrogen Plant: A Comparative Analysis of Production Methods - Mohammad Sajjadi; Hussameldin Ibrahim (Energies)
Blue hydrogen is a key pathway for reducing greenhouse gas emissions while utilizing natural gas with carbon capture and storage (CCS). This study conducts a techno-economic and environmental analysis of a greenfield blue hydrogen plant in Saskatchewan, Canada, integrating both SMR and ATR technologies. Unlike previous studies that focus mainly on production units, this research includes all process and utility systems such as H2 and CO2 compression, air separation, refrigeration, co-generation, and gas dehydration. Aspen HYSYS simulations revealed ATR’s energy demand is 10% lower than that of SMR. The hydrogen production cost was USD 3.28/kg for ATR and USD 3.33/kg for SMR, while a separate study estimated a USD 2.2/kg cost for design without utilities, highlighting the impact of indirect costs. Environmental analysis showed ATR’s lower Global Warming Potential (GWP) compared to SMR, reducing its carbon footprint. The results signified the role of utility integration, site conditions, and process selection in optimizing energy efficiency, costs, and sustainability.